Angklung Kota Bandung Menembus Masa - Mila Mardotillah (Tourism, Hospitality And Culture Insights Journal, 2023)
The objects of cultural development in Bandung city which is very developed is the art of Angklung. Angklung is one of the typical arts of West Java that has been around for a long time. The existence of Angklung in Bandung city has existed since 1930 before Indonesia's independence. Pioneered by Daeng Soetigna, angklung developed in Bandung from the pentatonic scale to the diatonic scale. The aim of this research is to describe the existence of Angklung in Bandung City as an ecosystem in Bandung City. The method used is descriptive qualitative by exploring the role of all members of the community from craftsmen to academics in maintaining the existence of Angklung in Bandung City. The results show that all categories of community who are involved and related to the art of angklung carry out preservation based on their respective roles, either groups of traditional, modern or contemporary Angklung players. The conclusion of this research is that every member of the community who is related to the art of Angklung, including the Angklung community, Angklung craftsmen, Angklung artists, academics, trainers and Angklung teachers have a major role in maintaining the existence of Angklung from time to time in Bandung city as a cultural heritage and cultural destination.